Thermal properties of nylon6/ABS polymer blends: Compatibilizer effect - Araújo, E. M.; Hage, E.; Carvalho, A. J. F. (Springer Nature, 2004)
Nylon6/ABS binary blends are incompatible and need to be compatibilized to achieve better performance under impact tests. Poly(methyl methacrylate/maleic anhydride) (MMA-MA) is used in this work to compatibilize in situ nylon6/ABS immiscible blends. The MA functional groups, from MMA-MA copolymers, react with NH2 groups giving as products nylon molecules grafted to MMA-MA molecules. Those molecular species locate in the nylon6/ABS blend interfacial region increasing the local adhesion. MMA-MA segments are completely miscible with the SAN rich phase from the ABS. The aim of this work is to study the effects of ABS and compatibilizing agent on the melting and crystallization of nylon6/ABS blends. This effect has been investigated by differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA). Incorporation of this compatibilizer and ABS showed little effect on the melting behavior of the PA6 crystalline phase, in general. DMTA analysis confirmed the system immiscibility and showed evidence of compatibility between the two phases, nylon6 and ABS, produced by MMA-MA copolymer presence. The nylon6/ABS blend morphology, observed by transmission electron microscopy (TEM), changes significantly by the addition of the MMA-MA compatibilizer. A better dispersion of ABS in the nylon6 phase is observed. © 2004 Kluwer Academic Publishers.
Keywords: Crystallization; Differential scanning calorimetry; Impact testing; Melting; Morphology; Nylon polymers; Polymethyl methacrylates; Solubility; Thermoanalysis; Thermodynamic properties; Thermoplastics; Transmission electron microscopy; Compatibilizer effect; Dynamic mechanical thermal analysis; Maleic anhydride; Polymer blends